2015
DOI: 10.1002/ejic.201403041
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Dinitrogen Bound to Mid‐ and Late‐Transition‐Metal Centers

Abstract: This review presents a comprehensive overview of the reactions of N 2 within the coordination sphere of transition metals of groups 6 to 9. Many of these metals mediate the reaction of N 2 with protons under reductive conditions, which can lead to the (catalytic) formation of ammonia or hydrazine, and the mechanisms of these reactions somewhat resemble the mode of action of nitrogenase enzymes. Alternatively, coordinated N 2 can react with carbon and silicon electrophiles and radicals to allow, for example, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 135 publications
(123 reference statements)
1
54
1
Order By: Relevance
“…61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B. 165 The higher degree of Fe-heteroatom bond flexibility in 42 could be crucial for stabilizing the variety of N 2 reduction intermediates in the catalytic cycle.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…61,157,191,192,41,44,165 Peters has shown that phosphine ligands provide excellent platforms for functionalization of N 2 on iron, 60,193,194 and enable characterization of potential N 2 reduction intermediates Fe-N x H y , 98,99,165,194196 including systems that feature a coordinated hydride. 40,42,43 Ammonia production by tripodal trisphosphine ligands with an axial donor (Si, C, or B) increases in the order Si < C < B. 165 The higher degree of Fe-heteroatom bond flexibility in 42 could be crucial for stabilizing the variety of N 2 reduction intermediates in the catalytic cycle.…”
Section: Fe-nxhy Complexes With Sulfur Ligandsmentioning
confidence: 99%
“…6 This search has yielded systems capable of the catalytic reduction of N 2 to hydrazine (N 2 H 4 ), 7 tris(trimethylsilyl)amine, 8 and a few examples of the direct catalytic fixation of N 2 to NH 3 (Chart 1). 8g,9,10,11,12 While a wealth of mechanistic information for the original Mo catalyst system developed by Schrock has been derived from stoichiometric studies and theory, 13,14 in situ spectroscopic studies during catalysis were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…12 Germane to our present interest, the identification and study of a homologous, isostructural series of complexes (Fe, Ru, Os) will help to better delineate some of the key factors for N 2 RR catalyst design.…”
mentioning
confidence: 99%